Preparation method of high-strength magnesium alloy
By hot rolling and aging treatment of Mg-Gd-Y rare earth magnesium alloy, a high-strength magnesium alloy containing β" phase was generated, which solved the problem of low absolute strength of magnesium alloy and achieved efficient and low-cost high-strength magnesium alloy preparation .
Patent Information
- Application Number
- CN202411596159.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-07
AI Technical Summary
The absolute strength of existing magnesium alloys limits its further application in aerospace, rail transit and other fields.
By hot rolling and aging treatment of the Mg-Gd-Y rare earth magnesium alloy, a high-strength magnesium alloy containing the β" phase is generated, and the tensile strength is improved by using the uniform distribution and stability of the β" phase.
It realizes efficient preparation of high-strength magnesium alloys, improves tensile strength, solves the pain points in the strengthening process of rare earth magnesium alloys, and reduces aging time and cost.
Smart Images

Figure CN119392131A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of nonferrous metal materials, and in particular to a method for preparing a high-strength magnesium alloy. Background Art
[0002] Magnesium alloys have the advantages of low density, high specific strength and specific stiffness, and have been widely used in aerospace, rail transportation, military and national defense, etc. However, the disadvantage of low absolute strength of magnesium alloys has greatly restricted the further application of magnesium alloys, so the development of high-strength magnesium alloys has become an urgent need.
[0003] Alloying is a conventional method to improve the absolute strength of magnesium alloys, among which Mg-Gd-Y rare earth magnesium alloys have significant strength advantages, and the main strengthening mechanisms are solid solution strengthening and precipitation strengthening. At present, the main strengthening phase in the alloy is the rod-shaped β' phase, which generally requires a rare earth element content greater than 10wt%, but the strength of high-strength magnesium alloys prepared from alloys with a rare earth element content greater than 10wt% still needs to be improved. Summary of the invention
[0004] The invention provides a method for preparing a high-strength magnesium alloy. The high-strength magnesium alloy prepared by the invention has high strength.
[0005] The present invention provides a method for preparing a high-strength magnesium alloy, comprising the following steps:
[0006] The solid solution Mg-Gd-Y rare earth magnesium alloy is hot rolled and aged to obtain a high-strength magnesium alloy containing β" phase;
[0007] The total mass fraction of the Gd element and the Y element in the solid solution Mg-Gd-Y rare earth magnesium alloy is less than 10%.
[0008] Preferably, the element composition of the Mg-Gd-Y rare earth magnesium alloy is, by mass fraction, as follows:
[0009] The Gd element is 4.8-5.7%, the Y element is 3.8-4.6%, the Zr element is 0.09-0.14%, and the balance is the magnesium element and inevitable impurities.
[0010] Preferably, the mass ratio of the Gd element to the Y element is >1:1.
[0011] Preferably, the hot rolling direction is the length direction or width direction of the solid solution Mg-Gd-Y series rare earth magnesium alloy; and the total number of hot rolling passes is 9 to 13 passes.
[0012] Preferably, before each hot rolling, the process includes: heating the initial solid solution Mg-Gd-Y series rare earth magnesium alloy or the solid solution Mg-Gd-Y series rare earth magnesium alloy obtained by the previous hot rolling;
[0013] The heating temperature before each hot rolling is independently 400-500°C, and the heating and holding time is independently 10-15 minutes. 。
[0014] Preferably, the speed of each hot rolling pass is independently 4 to 8 m / min.
[0015] Preferably, the pressing amount of each hot rolling pass is independently 2 to 10%;
[0016] The total reduction amount of the hot rolling is 47-53%.
[0017] Preferably, the method for preparing the solid solution Mg-Gd-Y series rare earth magnesium alloy comprises the following steps:
[0018] Solvent-dissolving a Mg-Gd-Y series rare earth magnesium alloy;
[0019] The solid solution temperature is 480-500° C. and the time is 5.5-6.5 hours.
[0020] Preferably, the aging treatment is carried out at a temperature of 190 to 210° C. and for a time of 16 to 96 hours.
[0021] Preferably, the particle size of the β" phase is 2 to 10 nm.
[0022] The present invention enables the rare earth magnesium alloy to generate a large amount of β" phase uniformly dispersed in the rare earth magnesium alloy after aging treatment through the component content of the Mg-Gd-Y series rare earth magnesium alloy, and the generated β" phase cannot be further transformed into β' phase due to the low rare earth content, so that the generated β" phase can be retained. The retained β" phase can greatly hinder the movement of dislocations and the growth of grain boundaries, thereby greatly improving the tensile strength of the rare earth magnesium alloy.
[0023] Rare earth magnesium alloys with β" phase as the main strengthening phase no longer rely on increasing the rare earth element content as the only strengthening method, and are not restricted by the maximum solid solubility. They successfully solve the pain points in the current strengthening process of rare earth magnesium alloys, shorten the aging time, and achieve high-efficiency preparation of low-cost and high-strength magnesium alloys. It provides a new strengthening idea for it and is an advanced method for preparing high-strength magnesium alloys. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The metallographic images of the rectangular plate (solid solution state), the hot rolled rectangular plate (rolled state) and the high-strength magnesium alloy samples obtained at different aging times in Example 3;
[0025] Figure 2 This is the morphology of the precipitation phase in the high-strength magnesium alloy sample aged for 80 hours in Example 3;
[0026] Figure 3 The engineering stress-strain curves of the rectangular plate (solid solution state), the hot-rolled rectangular plate (rolled state) and the high-strength magnesium alloy samples obtained at different aging times in Example 3;
[0027] Figure 4 The metallographic images of the rectangular plate (solid solution state), the hot rolled rectangular plate (rolled state) and the high-strength magnesium alloy samples obtained at different aging times in Example 4;
[0028] Figure 5 This is the morphology of the precipitation phase in the high-strength magnesium alloy sample aged for 32 hours in Example 4;
[0029] Figure 6 The engineering stress-strain curves of the rectangular plate (solid solution state), the hot-rolled rectangular plate (rolled state) and the high-strength magnesium alloy samples obtained at different aging times in Example 4 are shown. DETAILED DESCRIPTION
[0030] The present invention provides a method for preparing a high-strength magnesium alloy, comprising the following steps:
[0031] The solid solution Mg-Gd-Y rare earth magnesium alloy is subjected to solid solution treatment, hot rolling and aging treatment to obtain a high-strength magnesium alloy containing β" phase;
[0032] The total mass fraction of the Gd element and the Y element in the solid solution Mg-Gd-Y rare earth magnesium alloy is less than 10%.
[0033] In the present invention, the total mass fraction of the Gd element and the Y element in the solid solution Mg-Gd-Y series rare earth magnesium alloy is less than 10%. In a specific embodiment of the present invention, the total mass fraction of the Gd element and the Y element in the Mg-Gd-Y series rare earth magnesium alloy can be 5%, 6%, 7%, 8%, 9%, 9.4%, 9.5% or 9.9%; the mass ratio of the Gd element to the Y element is preferably greater than 1:1. In a specific embodiment of the present invention, the mass ratio of the Gd element to the Y element can be 24:23, 53:41, 57:38 or 3:1.
[0034] In the present invention, the element composition of the Mg-Gd-Y series rare earth magnesium alloy preferably includes 4.8-5.7% of Gd element by mass fraction. In a specific embodiment of the present invention, the mass fraction of the Gd element in the Mg-Gd-Y series rare earth magnesium alloy may be 4.8%, 5.3% or 5.7%. The Gd element can provide higher solid solution strengthening and easily form a second phase with the Mg element.
[0035] In the present invention, the element composition of the Mg-Gd-Y series rare earth magnesium alloy preferably includes 3.8-4.6% of Y element by mass fraction. In a specific embodiment of the present invention, the mass fraction of the Y element in the Mg-Gd-Y series rare earth magnesium alloy can be 3.8%, 4.1% or 4.6%. The introduction of the Y element can also provide higher solid solution strengthening, and it is also easy to form a second phase with the Mg element. The Y element is introduced together with the Gd element, and the Y element can replace the Gd element to a certain extent.
[0036] In the present invention, the element composition of the Mg-Gd-Y series rare earth magnesium alloy preferably includes 0.09-0.14% Zr element in terms of mass fraction. In a specific embodiment of the present invention, the mass fraction of the Zr element in the Mg-Gd-Y series rare earth magnesium alloy can be 0.09%, 0.13% or 0.14%.
[0037] In the present invention, the composition of the Mg-Gd-Y rare earth magnesium alloy preferably includes the balance of magnesium element and inevitable impurities, measured by mass fraction;
[0038] In the present invention, the method for preparing the solid solution Mg-Gd-Y series rare earth magnesium alloy preferably comprises the following steps:
[0039] The Mg-Gd-Y series rare earth magnesium alloy is solid-solutionized.
[0040] In the present invention, the solid solution temperature is preferably 480-500°C. In a specific embodiment of the present invention, the solid solution temperature may be 480°C, 490°C or 500°C. The time is preferably 5.5-6.5h. In a specific embodiment of the present invention, the solid solution time may be 5.5h, 6h or 6.5h.
[0041] When the solid solution Mg-Gd-Y series rare earth magnesium alloy is in the shape of an ingot, before the hot rolling, the present invention preferably cuts and grinds the solid solution Mg-Gd-Y series rare earth magnesium alloy to obtain a solid solution Mg-Gd-Y series rare earth magnesium alloy sheet to be hot rolled.
[0042] In the present invention, the hot rolling direction is preferably the length direction or the width direction of the Mg-Gd-Y series rare earth magnesium alloy.
[0043] In the present invention, the total number of hot rolling passes is preferably 9 to 13 passes. In a specific embodiment of the present invention, the total number of hot rolling passes may be 9 passes, 10 passes, 11 passes, 12 passes or 13 passes.
[0044] In the present invention, before each hot rolling, the present invention preferably includes: heating the initial solid solution Mg-Gd-Y series rare earth magnesium alloy or the solid solution Mg-Gd-Y series rare earth magnesium alloy obtained by the previous hot rolling; the heating temperature before each hot rolling is independently 400-500°C. In a specific embodiment of the present invention, the heating temperature before each hot rolling can be 400°C, 450°C or 500°C; the holding time is independently 10-15min. In a specific embodiment of the present invention, the heating and holding time before each hot rolling can be independently 10min, 11min, 12min, 13min, 14min or 15min. 。
[0045] In the present invention, the speed of each hot rolling pass is preferably independently 4 to 8 m / min. In a specific embodiment of the present invention, the speed of each hot rolling pass can be independently 4 m / min, 5 m / min, 6 m / min, 7 m / min or 8 m / min.
[0046] In the present invention, the pressing amount of each hot rolling pass is preferably independently 2-10%. In a specific embodiment of the present invention, the pressing amount of each hot rolling pass can be independently 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%;
[0047] In the present invention, the total pressing amount of hot rolling is preferably 47-53%. In a specific embodiment of the present invention, the total pressing amount of hot rolling can be 47%, 48%, 49%, 50%, 51%, 52% or 53%.
[0048] In the present invention, the obtained Mg-Gd-Y series rare earth magnesium alloy and the rollers used are preferably cooled after each hot rolling; the cooling method is preferably air cooling, and the temperature after cooling is preferably room temperature.
[0049] In the present invention, the temperature of the aging treatment is preferably 190-210°C. In a specific embodiment of the present invention, the temperature of the aging treatment may be 190°C, 200°C or 210°C. The time is preferably 16-96h. In a specific embodiment of the present invention, the time of the aging treatment may be 16h, 32h, 48h, 60h, 72h, 80h or 96h.
[0050] In the present invention, the particle size of the β" phase is preferably 2 to 10 nm. In a specific embodiment of the present invention, the particle size of the β" phase may be 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm.
[0051] The preparation method of the high-strength magnesium alloy provided by the present invention is described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0052] Example 1
[0053] (1) Using the Mg-4.8Gd-4.6Y-0.09Zr cylindrical alloy ingot after solution treatment at 480℃×6h as the raw material, magnesium alloy discs with a thickness of 3mm and a diameter of 86mm were cut perpendicular to the cylindrical axis.
[0054] (2) With a diagonal length of 86 mm, a rectangular plate with a size of 70 mm × 50 mm × 3 mm was cut from a magnesium alloy disc, and each surface of the rectangular plate was polished with 240#, 400#, and 1000# sandpaper in sequence until the surface was bright and there were no scratches visible to the naked eye under natural light.
[0055] (3) Hot rolling is performed along a length of 70 mm at a hot rolling speed of 4 m / min.
[0056] (4) In step (3), the hot rolling is performed for a total of 9 passes. Before each hot rolling pass, the hot rolling is subjected to a heat preservation treatment at 400°C for 15 min in a box-type resistance furnace. After each hot rolling pass, the hot rolling is cooled by air, and the temperature of the rolling rollers is at room temperature.
[0057] (5) In step (3), the pressing amount of the first two passes is 6%, and the pressing amount of the remaining passes is 5%, with a total pressing amount of 47%.
[0058] (6) The hot-rolled plates were subjected to aging treatment at 200° C. in a tubular heating furnace. The aging time was 16 h, 32 h, 64 h, 80 h, and 96 h. The cooling method of the plates after aging treatment was air cooling.
[0059] (7) The room temperature tensile strength test of the high-strength magnesium alloy sample containing highly dispersed nano-precipitates obtained in Example 1 was carried out. The test was carried out in accordance with GB / T228.1-2010 "Tensile test of metallic materials - Part 1: Room temperature test method". The tensile rate was 0.5 mm / min. The Vickers hardness of the high-strength magnesium alloy samples prepared with aging time of 16 h, 32 h, 64 h, 80 h, and 96 h were 92.5, 96.3, 109.8, 100.2, and 104.1, respectively. The tensile strength of the high-strength magnesium alloy sample prepared with peak aging time of 64 h was 441 MPa.
[0060] Example 2
[0061] (1) Using the Mg-5.7Gd-3.8Y-0.14Zr cylindrical alloy ingot after solution treatment at 500℃×6h as the raw material, magnesium alloy discs with a thickness of 3mm and a diameter of 93mm were cut perpendicular to the axial direction of the cylinder.
[0062] (2) With a diagonal length of 93 mm, a rectangular plate with a size of 75 mm × 55 mm × 3 mm was cut from a magnesium alloy disc, and each surface of the rectangular plate was polished with 240#, 400#, and 1000# sandpaper in sequence until the surface was bright and there were no scratches visible to the naked eye under natural light.
[0063] (3) The plate is hot rolled along a length of 75 mm at a speed of 8 m / min.
[0064] (4) In step (3), the hot rolling is performed for a total of 13 passes. Before each hot rolling pass, the hot rolling is subjected to a heat preservation treatment at 500°C for 10 min in a box-type resistance furnace. After each hot rolling pass, the hot rolling is cooled by air, and the temperature of the rolling rollers is at room temperature.
[0065] (5) In step (3), the pressing amount of the first three passes is 10%, the pressing amount of the last pass is 5%, and the pressing amount of the remaining passes is 2%, with a total pressing amount of 53%.
[0066] (6) The hot-rolled plates were subjected to aging treatment at 200° C. in a tubular heating furnace. The aging time was 16 h, 32 h, 64 h, 80 h, and 96 h. The cooling method of the plates after aging treatment was air cooling.
[0067] (7) The room temperature tensile strength test of the high-strength magnesium alloy sample containing highly dispersed nano-precipitates obtained in Example 2 was carried out. The test was carried out in accordance with GB / T228.1-2010 "Tensile test of metallic materials - Part 1: Room temperature test method". The tensile rate was 0.5 mm / min. The Vickers hardness of the high-strength magnesium alloy samples prepared with aging time of 16 h, 32 h, 64 h, 80 h, and 96 h were 93.3, 94.9, 97.0, 111.7, and 102.8, respectively. The tensile strength of the high-strength magnesium alloy sample prepared with peak aging time of 80 h was 452 MPa.
[0068] Example 3
[0069] (1) Using the Mg-5.3Gd-4.1Y-0.13Zr cylindrical alloy ingot after solution treatment at 480℃×6h as the raw material, magnesium alloy discs with a thickness of 3mm and a diameter of 90mm were cut perpendicular to the cylindrical axis.
[0070] (2) With a diagonal length of 90 mm, a rectangular plate with a size of 75 mm × 50 mm × 3 mm was cut from a magnesium alloy disc, and each surface of the rectangular plate was polished with 240#, 400#, and 1000# sandpaper in sequence until the surface was bright and there were no scratches visible to the naked eye under natural light.
[0071] (3) The plate is hot rolled along a length of 75 mm at a speed of 6 m / min.
[0072] (4) In step (3), the hot rolling is performed for a total of 12 passes. Before each hot rolling pass, the hot rolling is subjected to a heat preservation treatment at 400°C for 15 min in a box-type resistance furnace. After each hot rolling pass, the hot rolling is cooled by air, and the temperature of the rolling rollers is at room temperature.
[0073] (5) In step (3), the pressing amount in the first pass is 9%, the pressing amount in the next six passes is 5%, and the pressing amount in the remaining passes is 2%, with a total pressing amount of 49%.
[0074] (6) The hot-rolled plates were subjected to aging treatment at 200° C. in a tubular heating furnace. The aging time was 16 h, 32 h, 64 h, 80 h, and 96 h. The cooling method of the plates after aging treatment was air cooling.
[0075] (7) The high-strength magnesium alloy sample containing highly dispersed nano-precipitates obtained in Example 3 was subjected to a room temperature tensile strength test. The tensile specimens were sampled along the hot rolling direction. The test was carried out in accordance with GB / T228.1-2010 "Tensile test of metallic materials Part 1: Room temperature test method". The tensile rate was 0.5 mm / min, and the aging time was 16 h, 32 h, 64 h, 80 h, and 96 h. The tensile strengths of the high-strength magnesium alloy samples prepared were 289 MPa, 249 MPa, 318 MPa, 504 MPa, and 301 MPa, respectively.
[0076] Figure 1 Metallographic images of the rectangular plate (solid solution state), the hot-rolled rectangular plate (rolled state) and the high-strength magnesium alloy samples obtained at different aging times in Example 3.
[0077] Depend on Figure 1 It can be seen that, except for the solid solution state, the grain sizes in other states are relatively close, most of the grain sizes are between 35 and 65 μm, and no obvious grain refinement strengthening behavior occurs.
[0078] Figure 2 This is the morphology of the precipitation phase in the high-strength magnesium alloy sample aged for 80 hours in Example 3.
[0079] Depend on Figure 2 It can be seen that the precipitated phase is ellipsoidal in shape and has a size of 2 to 6 nm. It belongs to the nanoscale precipitated phase and is uniformly dispersed in the matrix. It can effectively hinder dislocations and pin grain boundaries, so that the material obtains higher strength.
[0080] Figure 3 The engineering stress-strain curves of the rectangular plate (solid solution state), the hot-rolled rectangular plate (rolled state) and the high-strength magnesium alloy samples obtained at different aging times in Example 3.
[0081] Depend on Figure 3 It can be seen that the material in Example 1 reaches peak aging at 80 h, at which time the tensile strength of the material reaches 504 MPa, which belongs to the category of high-strength magnesium alloy.
[0082] Example 4
[0083] (1) Using the Mg-5.3Gd-4.1Y-0.13Zr cylindrical alloy ingot after solution treatment at 480℃×6h as the raw material, magnesium alloy discs with a thickness of 3mm and a diameter of 90mm were cut perpendicular to the cylindrical axis.
[0084] (2) With a diagonal length of 90 mm, a rectangular plate with a size of 75 mm × 50 mm × 3 mm was cut from a magnesium alloy disc, and each surface of the rectangular plate was polished with 240#, 400#, and 1000# sandpaper in sequence until the surface was bright and there were no scratches visible to the naked eye under natural light.
[0085] (3) The plate is hot rolled along a length of 75 mm at a speed of 6 m / min.
[0086] (4) In step (3), the hot rolling is performed for a total of 12 passes. Before each hot rolling pass, the hot rolling is subjected to a heat preservation treatment at 400°C for 15 min in a box-type resistance furnace. After each hot rolling pass, the hot rolling is cooled by air, and the temperature of the rolling rollers is at room temperature.
[0087] (5) In step (3), the pressing amount in the first pass is 9%, the pressing amount in the next six passes is 5%, and the pressing amount in the remaining passes is 2%, with a total pressing amount of 49%.
[0088] (6) The hot-rolled plates were subjected to aging treatment at 200° C. in a tubular heating furnace. The aging time was 16 h, 32 h, 64 h, 80 h, and 96 h. The cooling method of the plates after aging treatment was air cooling.
[0089] (7) The high-strength magnesium alloy sample containing highly dispersed nano-precipitates obtained in Example 4 was subjected to a room temperature tensile strength test. The tensile specimens were sampled along the hot rolling direction. The test was carried out in accordance with GB / T228.1-2010 "Tensile test of metallic materials Part 1: Room temperature test method". The tensile strengths of the high-strength magnesium alloy samples prepared with aging times of 16h, 32h, 64h, 80h, and 96h were 302MPa, 512MPa, 423MPa, 437MPa, and 326MPa, respectively.
[0090] Figure 4 Metallographic images of the rectangular plate (solid solution state), the hot-rolled rectangular plate (rolled state) and the high-strength magnesium alloy samples obtained at different aging times in Example 4.
[0091] Depend on Figure 4 It can be seen that, except for the solid solution state, the grain sizes in other states are relatively close, most of the grain sizes are between 30 and 65 μm, and no obvious grain refinement strengthening behavior occurs.
[0092] Figure 5 This is the morphology of the precipitation phase in the high-strength magnesium alloy sample aged for 32 hours in Example 4.
[0093] Depend on Figure 5 It can be seen that the precipitated phase is ellipsoidal with a size of 1 to 7 nm, which is a nanoscale precipitated phase and is uniformly dispersed in the matrix. It can effectively hinder dislocations and pin grain boundaries, so that the material obtains higher strength.
[0094] Figure 6 The engineering stress-strain curves of the rectangular plate (solid solution state), the hot-rolled rectangular plate (rolled state) and the high-strength magnesium alloy samples obtained at different aging times in Example 4 are shown.
[0095] Depend on Figure 6 It can be seen that the material in Example 1 reaches peak aging at 32 hours, at which time the tensile strength of the material reaches 512 MPa, which belongs to the category of high-strength magnesium alloy.
[0096] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a high-strength magnesium alloy, characterized in that: The following steps are involved: The solid solution Mg-Gd-Y rare earth magnesium alloy is hot rolled and aged to obtain a high-strength magnesium alloy containing β" phase; The total mass fraction of the Gd element and the Y element in the solid solution Mg-Gd-Y rare earth magnesium alloy is less than 10%.
2. The preparation method according to claim 1, characterized in that: In terms of mass fraction, the element composition of the solid solution Mg-Gd-Y rare earth magnesium alloy is: The Gd element is 4.8-5.7%, the Y element is 3.8-4.6%, the Zr element is 0.09-0.14%, and the balance is the magnesium element and inevitable impurities.
3. The preparation method according to claim 1 or 2, characterized in that: The method for preparing the solid solution Mg-Gd-Y rare earth magnesium alloy comprises the following steps: Solvent-dissolving a Mg-Gd-Y series rare earth magnesium alloy; The solid solution temperature is 480-500° C. and the time is 5.5-6.5 hours.
4. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the Gd element to the Y element is greater than 1:
1.
5. The preparation method according to claim 1, characterized in that: The hot rolling direction is the length direction or width direction of the solid solution Mg-Gd-Y series rare earth magnesium alloy; the total number of hot rolling passes is 9 to 13 passes.
6. The preparation method according to claim 5, characterized in that: Before each hot rolling, the method comprises: heating the initial solid solution Mg-Gd-Y series rare earth magnesium alloy or the solid solution Mg-Gd-Y series rare earth magnesium alloy obtained by the previous hot rolling; The heating temperature before each hot rolling is independently 400-500°C, and the heating and holding time is independently 10-15 minutes. 。 7. The preparation method according to claim 5 or 6, characterized in that: The speed of each hot rolling pass is independently 4 to 8 m / min.
8. The preparation method according to claim 5 or 6, characterized in that: The reduction amount of each hot rolling pass is independently 2 to 10%; The total reduction amount of the hot rolling is 47-53%.
9. The preparation method according to claim 1, characterized in that: The temperature of the aging treatment is 190-210° C., and the time is 16-96 hours.
10. The preparation method according to claim 1 or 9, characterized in that: The particle size of the β" phase is 2 to 10 nm.
Citation Information
Cited By
High-strength rare earth magnesium alloy deformed material and preparation method thereof
CN121852783A